Design and Construction of a Smartphone Based Beverage Vending Machine for Smes in the City of Balikpapan - Muheimin, M Rifki; Vidy, Vidy; Safii, Muhammad; Muliansyah, Nur (Sebatik, 2024)
Vending machines are automated goods-selling devices that operate without the need for an operator, allowing consumers to select the goods they want. These machines typically dispense drinks or snacks independently. A common issue with traditional vending machines is the lack of a refund system, which requires consumers to have the exact change to make a purchase. This study focuses on the design and development of a smart vending machine controlled via an Android smartphone application, specifically targeting Micro, Small, and Medium Enterprises (MSMEs) in Balikpapan, Indonesia. The research aims to ensure user adoption of the new system. During the development process, relevant literature and existing implementations were analyzed, leading to the decision to create a vending machine that supports payments without relying exclusively on Android or other platform-based devices. Drink menus are selected using automated technologies that analyze consumer demand for various types of beverages. The goal of this research is to assist MSMEs in independently marketing drinks online and to enhance consumer convenience through the use of advanced technology. A prototype was developed and tested in field trials to collect user feedback, and the findings are discussed in this study.